Normalizing India Pakistan trade - Nisha Taneja; Mishita Mehra; Prithvijit Mukherjee; Samridhi Bimal; Isha Dayal (Indian Council for Research on International Economic Relations (ICRIER), 2013)
With the trade normalization process between India and Pakistan gathering momentum since November 2011, new opportunities for enhancing bilateral trade have opened between the two countries. This study estimates the trade potential between India and Pakistan, and examines how this potential can be realized. Using the Trade Possibility Approach for all items traded, followed by selecting only those items in which the countries have a Revealed Comparative Advantage (RCA) to export, the trade potential between India and Pakistan is estimated to lie between US10.9 billion and US19.8 billion. Of the US10.9 billion trade potential, India's export potential accounts for US7.9 billion and import potential US3 billion. With a large number of items belonging to the negative or sensitive lists, the study estimates the trade potential accounted for by these items. Sectorwise analysis depicts that bilateral trade shall receive a boost if the textile sector is liberalized in both countries, with Pakistan liberalizing its automobile sector too. In the services sector, trade possibilities have been identified in Information Technology (IT), Business Process Outsourcing (BPO), health and entertainment services. The study finds that this trade potential remains unrealized largely due to impediments in transport and transit facilities, restrictive visa regime, continuation of large informal trade flows, and presence of 'perceived' non-tariff barriers to trade between India and Pakistan. As the Foreign Direct Investment (FDI) regime between the two countries is liberalized, the study identifies sectors which hold potential for investments, and are likely to deepen the trade linkages between India and Pakistan.
Keywords: F10; F13; F50; F53; 330; India-Pakistan; bilateral trade; trade normalization; trade potential; MFN; regional integration